Encapsulation of drug into mesoporous silica by solvent evaporation: A comparative study of drug characterization in mesoporous silica with various molecular weights - Arif Budiman; Diah Lia Aulifa (Heliyon, 2021)
Mesoporous silica (MS) is a promising material as a drug carrier that is used in pharmaceutical applications. It was discovered that the incorporation of drugs into MS has the potential to improve their dissolution and bioavailability due to the large specific surface area. This study aimed to characterize the drugs with various molecular weights in MS as well as to elucidate their impact on the loading amount and the amorphization within MS. The solvent evaporation method was used to encapsulate itraconazole (ITZ), nifedipine (NIF), and nicotinamide (NIC), respectively, into MS. The result shows the absence of glass transition and the melting peak of ITZ, NIF, and SAC within MS signifying the successful encapsulation. A hallo pattern was found in ITZ and NIF within MS indicating the amorphization. The high molecular weight and the interaction between the drug with the silica surface is reportedly contributed to the formation of the amorphous state. Meanwhile, the characteristic diffraction peaks of NIC crystal were observed for NIC within MS. In conclusion, the molecular weight of the drug has a significant effect on the loading amount and the amorphization of the drug within MS.